Insulin sensitisers in the treatment of non-alcoholic fatty liver disease: a systematic review - D Shyangdan (Health Technology Assessment, 2011)
Background: Non-alcoholic fatty liver disease (NAFLD) is closely linked with obesity and the prevalence of NAFLD is about 17% to 33% in the Western world. There is a strong association of NAFLD with insulin resistance and, hence, insulin sensitisers have been tried. This systematic review examined the clinical effectiveness of insulin sensitisers in patients with NAFLD, to help decide whether or not a trial or trials of the insulin sensitisers was necessary and also to explore whether or not non-invasive alternatives to liver biopsy were available that could be used in a large trial of the insulin sensitisers. Objective: To review the use of insulin sensitisers in the treatment of NAFLD. Review methods: A systematic review of the clinical effectiveness of metformin, rosiglitazone and pioglitazone was carried out, including reviews and randomised controlled trials (RCTs). Databases searched were MEDLINE, 1950 to June 2010; EMBASE, 1980 to June 2010; Science Citation Index Expanded, June 2010; Conference Proceedings Citation Index – Science June 2010; The Cochrane Library 2005–10. Abstracts were screened independently by two researchers. A narrative review of diagnostic methods was conducted. Results: Clinical effectiveness. We identified 15 RCTs (one available as abstract). Four papers explored efficacy of pioglitazone, one rosiglitazone, eight metformin; two compared metformin and rosiglitazone, although one used both metformin and rosiglitazone. The duration of most trials was between 6 and 12 months. Many trials had a small number of participants and the quality of the studies was mixed. Pioglitazone improved all parameters of liver histology. Metformin showed mixed results, with ultrasound changes in two studies showing some improvement in steatosis, whereas there were no changes in the other two. Metformin, however, showed no improvement in non-alcoholic steatohepatitis (NASH) stages. Metformin showed greater reduction in glycosylated haemoglobin (–0.23% to –1.2% vs –0.2% to –0.7%) and fasting plasma glucose (+0.05 to –3.19 mmol/l vs –0.17 to –1.11 mmol/l) compared with pioglitazone. Metformin led to weight reduction (–4.3 to –6.7 kg), whereas participants on pioglitazone gained weight (+2.5 to +4.7 kg). Alanine aminotransferase levels were reduced with both metformin and pioglitazone; however, the reduction in levels with pioglitazone was not different to that caused by vitamin E. Most studies suggested that metformin led to a significant reduction in insulin resistance. Diagnosis. Non-invasive methods of diagnosing NAFLD without liver biopsy, using combinations of clinical history, laboratory tests and ultrasound, have been explored, but so far liver biopsy is the only proven method of distinguishing simple steatosis from NASH. Transient elastography appears useful, but less so in obese individuals. Magnetic resonance spectroscopy shows promise, but is expensive and not readily available. Limitations: Mixed quality of trials, with lack of detail as to how some trials were conducted. Many trials had small numbers of patients. Conclusions: The main need for drug trials is at the NASH stage. However, at present, any trial in the more advanced forms of NAFLD would have to use liver biopsy. The highest priority for research may, therefore, be in the diagnosis of NAFLD, and the differentiation between steatosis and NASH. The newer agents, the glucagon-like peptide-1 analogues such as liraglutide, may be more worthy of a trial. Funding: The National Institute for Health Research Health Technology Assessment programme.